Kinerja Konselor Ditinjau dari Kompetensi Profesional di SMA Negeri Se-Kabupaten Batang - Sari, Nichien; Hartati, M.Th Sri (Indonesian Journal of Guidance and Counseling: Theory and Application, 2013)
This study was conducted based on the phenomenon of school counseling teachers that performance is not optimal. Guidance and counseling services in group format and individual format are not optimal. Besides the preparation of programs that are not based on need assessment results indicate the implementation of instrumentation and data applications are not implement optimally. This study uses a quantitative method with a descriptive approach. The population are all of the counseling teachers in Batang State High School with number 25 counseling teachers. Therefore, the subject is less than 100, so this study used a population sample. The instrument that used in this study was a questionnaire. Data were analyzed using descriptive analysis of the percentage. Descriptive analysis of data obtained percentage counselor performance in terms of professional competence in Batang State High School is high (83.1%). The conclusions of this study which counselors Batang State High School has been able to mastering and apply their professional competence in the implementation of guidance and counseling services with high criteria.